2015
DOI: 10.3109/14756366.2015.1029471
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase IX correlates with survival and is a potential therapeutic target for neuroblastoma

Abstract: Carbonic anhydrase IX (CAIX) is involved in pathological processes including tumorgenicity, metastases and poor survival in solid tumors. Twenty-two neuroblastoma samples of patients who were surgically treated at the University Medical Center Hamburg-Eppendorf were evaluated immunohistochemically for expression of CAIX. Results were correlated with clinical parameters and outcome. Neuroblastoma Kelly and SH-EP-Tet-21/N cells were examined for CAIX expression and inhibited with specific inhibitors, FC5-207A an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 37 publications
(58 reference statements)
3
28
0
Order By: Relevance
“…CAIX is expressed in specific types of tumors as a mediator of the complex response to the low-oxygen environment [ 66 ]. In NB, a correlation between up-regulation of CAIX expression and poor survival, particularly in MYCN -amplified tumors, has been shown [ 89 , 90 ]. Our study revealed that the strong inhibition of angiogenesis by the KD combined with low-dose cyclophosphamide did not stimulate a hypoxic response in NB.…”
Section: Discussionmentioning
confidence: 99%
“…CAIX is expressed in specific types of tumors as a mediator of the complex response to the low-oxygen environment [ 66 ]. In NB, a correlation between up-regulation of CAIX expression and poor survival, particularly in MYCN -amplified tumors, has been shown [ 89 , 90 ]. Our study revealed that the strong inhibition of angiogenesis by the KD combined with low-dose cyclophosphamide did not stimulate a hypoxic response in NB.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CAIX expression represents a common cancer cell adaptation to changes in tumour microenvironment, such as hypoxia and acidosis, both involved in cancer progression and resistance. CAIX expression in human tumour samples is always associated with tumour progression and poor prognosis 12–16 and its block through chemical inhibitors, either as a single treatment or in combination with radiotherapy, significantly reduces tumour growth in vivo 17 , 18 . Moreover, CAIX targeting by Acetazolamide treatment enhances the anti-angiogenic effect of Bevacizumab 19 .…”
Section: Introductionmentioning
confidence: 99%
“…These CA families are found in most living organisms. For example a-CAs are found in humans and other mammals and divided into four broad subgroups, which, in turn consist of several isoforms: the cytosolic CAs (CA I, II, III, VII, and XIII), mitochondrial CAs (CA VA and VB), secreted CA (CA VI), as well as membraneassociated CAs (CA IV, IX, XII, XIV and XV) [20][21][22][23][24] . There are three additional, acatalytic CA isoforms (CA VIII, X, and XI) whose functions remain unclear.…”
Section: Introductionmentioning
confidence: 99%